2019
DOI: 10.1111/faf.12425
|View full text |Cite
|
Sign up to set email alerts
|

Electronic monitoring in fisheries: Lessons from global experiences and future opportunities

Abstract: Since the beginning of the 21st century, electronic monitoring (EM) has emerged as a cost‐efficient supplement to existing catch monitoring programmes in fisheries. An EM system consists of various activity sensors and cameras positioned on vessels to remotely record fishing activity and catches. The first objective of this review was to describe the state of play of EM in fisheries worldwide and to present the insights gained on this technology based on 100 EM trials and 12 fully implemented programmes. Despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(61 citation statements)
references
References 62 publications
0
46
0
Order By: Relevance
“…Compliance monitoring of Lumo Leads, GloLeads and Hookpods through dockside monitoring would be relatively weak: during the fishing trip, crew could easily change the position of the Lumo Leads/GloLeads on leaders, and fishers might not attach Hookpods to hooks during setting. If, in the distant future, compliance monitoring occurs for 100% of pelagic longline fishing effort, such as through the use of electronic monitoring systems (Gilman et al 2019, van Helmond et al 2020, then branchline designs that currently do not support compliance monitoring will be better options. Until then, consideration of the capacity of a bycatch mitigation method to facilitate surveillance through dockside monitoring remains necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Compliance monitoring of Lumo Leads, GloLeads and Hookpods through dockside monitoring would be relatively weak: during the fishing trip, crew could easily change the position of the Lumo Leads/GloLeads on leaders, and fishers might not attach Hookpods to hooks during setting. If, in the distant future, compliance monitoring occurs for 100% of pelagic longline fishing effort, such as through the use of electronic monitoring systems (Gilman et al 2019, van Helmond et al 2020, then branchline designs that currently do not support compliance monitoring will be better options. Until then, consideration of the capacity of a bycatch mitigation method to facilitate surveillance through dockside monitoring remains necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 situation has afforded us essentially with a test. The test has effectively shown that the assumptions and concerns of widespread telework at-scale were largely unfounded and warrant being revisited (Orgysko 2020, Thornton 2020); that is, our personnel are finding ways to adjust, and remain remarkably productive (Smith 2020, Thornton 2020. Although productive and still meeting many facets of our mission, we also do not want to overstate the ability of our personnel to maintain productivity given some of the unique challenges arising from work-from-home scenarios, especially over extended periods of time.…”
Section: Development Of Advice and Debate Of Scientifically-based Manmentioning
confidence: 99%
“…Machine learning powers algorithms that can detect fishing activity, transshipments at sea and vessels entering restricted areas or even turning off their signals 19 . Electronic monitoring of activity on board vessels can help spot excessive bycatch or potential illegal catch of species such as sharks 20,21 . The increasing use of e-documentation can reduce manipulation of catch figures, while blockchain technology promises full traceability of fish products from their origin to the end user 22 .…”
Section: Addressing Ocean Governancementioning
confidence: 99%